A Novel Exfoliation Strategy to Significantly Boost the Energy Storage Capability of Commercial Carbon Cloth. (6th May 2015) - Wang, Wang; Liu, Wenyue; Zeng, Yinxiang; Han, Yi; Yu, Minghao; Lu, Xihong; Tong, Yexiang
<x xml:space="preserve">Abstract</x> A facile and efficient electrochemical oxidation method to directly activated carbon cloth as an excellent electrode material for supercapacitors is reported. Flexible asymmetric supercapacitor devices based on activated carbon cloth anodes reach a remarkable energy density and excellent long‐term durability.